Using the PEMDAS method will allow you to solve the expression. First, (-10)-(-11)= 1. Then you would subtract the -10 which would give you -9 as your full answer!
Answer:
18.85 units
Step-by-step explanation:
c = 3.14 x d
1. x^2 + y^2 - 4x + 12y - 20 = 0 ---- (x-2)^2 + (y+6)^2 = 60
3. 3x^2+ 3y^2 + 12x +18y - 15 = 0 --- (x+2)^2 + (y+3)^2 = 18
5. 2x^2 + 2y^2 - 24x - 16y - 8 = 0 --- (x-6)^2 + (y-4)^2 = 56
I don't know the other two, hope I helped though.
Answer:
the answer is d
Step-by-step explanation:
Graph the parabola using the direction, vertex, focus, and axis of symmetry.
vertex- (5,0)
focus- (5,1/4)
axis of symmetry- x=5
directrix- y=-1/4
ps. can u mark me brainliest if i get this aswer right plz????
thank u!!!!
9514 1404 393
Answer:
(x, y) = (-1, -16) or (3, 0)
Step-by-step explanation:
Perhaps you want to solve the system of equations ...
- y = x^2 +2x -15
- y -4x = -12
Substituting the first expression for y into the second equation gives ...
x^2 +2x -15 -4x = -12
x^2 -2x -3 = 0 . . . . . . . . add 12
(x -3)(x +1) = 0 . . . . . . . factor
Solutions are the values of x that make the factors zero: x = 3, x = -1.
The corresponding values of y are ...
y = -12 +4x
y = -12 +4{-1, 3} = -12 +{-4, 12} = {-16, 0}
The solutions to the system are ...
(x, y) = (-1, -16) or (3, 0)